The Effectiveness of Expert-Centered Marriage in Improving the Ideal Image of the Spouse and the Perfectionism of Single Girls - Kavehi Sedehi , Somaye; Yousefi , Zahra; Torkan , Hajar (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The study was performed to compare the effectiveness of the educational intervention of the acceptance-commitment-based approach and the group choice theory approach in adolescent anxiety syndrome. Method: The research method had a quasi-experimental type with a pretest-posttest design and a two-month follow-up. The statistical population consisted of single girls in Isfahan in 2019, and 40 girls were randomly selected after screening and were randomly assigned to the experimental (n=20) and control (n=20) groups. The experimental group underwent 9 ninety-minute sessions of researcher-made expert-centered premarital training and the control group was on the waiting list. In the study, both groups were assessed at the pre-test, post-test, and follow-up stages using the Hill and Karen Marriage Perfectionism Questionnaire (2016), and the mental image of the ideal spouse by Yousefi (2011). The collected data were analyzed using the repeated-measures analysis of variance (ANOVA). Results: The results indicated that expert-centered premarital training was effective in improving marriage perfectionism (P= 0.001, F= 19.15), and the mental image of the ideal spouse (P= 0.006, F= 5.25), and the effect was stable at the follow-up stage. Conclusion: According to the results, expert-centered marriage training was a suitable method for modifying perfectionism and the mental image of the ideal spouse among single girls.